(untitled) (Web of Teachers: Inderscience Research, 2026)
This article is dedicated to studying the technology for developing future teachers’ pedagogical creativity competence based on the transformative education approach. Pedagogical creativity is defined as the teacher’s ability to create innovative approaches, develop new ideas, and solve pedagogical problems effectively during the educational process. The study analyzed the creative thinking levels of a sample group consisting of 111 teachers. The results showed that 27% of the participants had an average level of creative thinking, 38% had a high level, and the remaining participants demonstrated a low level of creative thinking. The study also explored the importance of the transformative education approach in developing pedagogical creativity and its application in practice. The article emphasizes the necessity of implementing modern technologies and methodologies to enhance pedagogical creativity competence. Furthermore, recommendations for developing creative thinking in the education system are provided.